2002
DOI: 10.1182/blood-2001-12-0228
|View full text |Cite
|
Sign up to set email alerts
|

Malarial anemia leads to adequately increased erythropoiesis in asymptomatic Kenyan children

Abstract: Malarial anemia is associated with a shift in iron distribution from functional to storage compartments. This suggests a relative deficit in erythropoietin production or action similar to that observed in other infections. Our study in Kenyan children with asymptomatic malaria aimed at investigating whether malaria causes increased erythropoiesis, and whether the erythropoietic response appeared appropriate for the degree of resulting anemia. Longitudinal and baseline data were used from a trial with a 2 ؋ 2 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
3
29
0
1
Order By: Relevance
“…33 Most previous studies have shown that Epo was appropriately raised in children from endemic areas and in nonimmune adults presenting with malaria and mild anemia. 7,[34][35][36] We also found raised concentrations of Epo in children with malarial anemia.…”
Section: Discussionmentioning
confidence: 99%
“…33 Most previous studies have shown that Epo was appropriately raised in children from endemic areas and in nonimmune adults presenting with malaria and mild anemia. 7,[34][35][36] We also found raised concentrations of Epo in children with malarial anemia.…”
Section: Discussionmentioning
confidence: 99%
“…104,105 However, several studies of malaria in African children suffering from malarial anemia have shown appropriately raised Epo concentrations. 25,[106][107][108] In fact, the Epo levels in malarial anemia are more than 3-fold higher when compared with anemic children without malaria. 72 It is possible that ineffective or inadequate Epo synthesis does contribute to malarial anemia in some settings, possibly related to age, ethnic origin, or presentation of the patient.…”
Section: Org Frommentioning
confidence: 99%
“…Malaria‐induced haemolysis may lead to accelerated or ineffective erythropoiesis and thus increased folate requirements. Plasmodium infection, however, both during illness episodes and in symptomless carriers, can also present with suppressed erythropoiesis (Verhoef et al , 2002), which would reduce folate requirements. In individuals with high levels of acquired immunity, the effect of Plasmodium on haemolysis and thus the increase in folate requirements is limited.…”
Section: Determinants Of Folate Requirements In Africamentioning
confidence: 99%